Transition of Chronic Pediatric Nephrological Patients to Adult Care Excluding Patients on Renal Replacement Therapy with Literature Review - Mirjam Močnik; Sonja Golob Jančič; Nataša Marčun Varda (MDPI AG, 2022)
(1) Background: The transition of children with chronic kidney disease to adult care has become a well-handled issue. However, other patients with normal or mildly decreased renal function also requiring further management and transition are neglected. (2) Methods: A questionnaire was sent to patients with kidney pathology, aged 17 years and older.(3) Results: The patients were mostly high-school (55%) or college students (39%), living with their parents (94%). One third did not know how their disease affected their choice of profession and reproductive health. Furthermore, 46% of the respondents did not know who would continue with their care, and 44% still had a primary pediatrician. (4) Conclusions: A review of the literature on the topic was performed and summarized here. Regular education is the key for successful transfer, not only in chronic kidney and transplant patients, but also in others in whom a decline in renal function can be expected in the future.